UJI EFEKTIFITAS SINBIOTIK KEFIR TEPUNG PISANG BATU TERHADAP KADAR GLUKOSA DARAH DAN KADAR PROFIL LIPID TIKUS MODEL SINDROM METABOLIK Eﬀectiveness Test of banana (Musa balbisiana) Flour Kefir Synbiotic on Blood Glucose Level and Lipid Profile Level in Metabolic Syndrome Rats Model - Taufik Maryusman; Christine Diane Dien; Santi Herlina Mail (Media Gizi Indonesia, 2021)
Metabolic Syndrome is a metabolic disorder characterized by hyperglycemia, hypertriglyceridemia, and dyslipidemia which can be repaired through synbiotics. This study is to analyzed the eﬀects of banana (Musa balbisiana) flour kefir synbiotic on blood glucose level and lipid profile level of Metabolic Syndrome rats. This is true experimental study with pre-posttest with control goup design of 24 male Sprague Dawley rats which were divided into 4 groups randomly. Negative control goup (K-) given standard food only, positive control group (K +) given standard food with High Fat Fructose Diet (HFFD), intervention group I (PI) and intervention group II (PII) were given standard food with HFFD and banana (Musa balbisiana) flour kefir synbiotic 1,8 ml/200 g weight/day (PI) and 3,6 ml/200 g weight/day (PII) for three weeks. Blood glucose level was analyzed using glucose oxidase-peroxidase amino antipyrine method, cholesterol level was analyzed using cholesterol oxidase-peroxidase amino antipyrine, and triglyceride level was analyze using glycerol 3 phosphate oxidase phenol amino phenazone method. Result of Analysis of Varian test shows significant diﬀerences in mean between group (p=0,000) followed by PostHoc Bonferroni test or Post Hoc Games-Howel test which showed a mean diﬀerence in the PI and PII groups. Banana (Musa balbisiana) flour kefir synbiotic can reduce blood glucose level and improve lipid profile level.